Trends in E-learning - Sinecen, Mahmut (IntechOpen, 2018)
This book presents a collection of different researches and results on "e-learning". The chapters cover the deficiencies, requirements, advantages and disadvantages of e-learning and distance learning. So, the authors reported their research and analysis results on "e-learning" according to their areas of expertise.